'A habitual disposition to the good': on reason, virtue and realism. Issue 2 (3rd April 2015) - Pabst,
Abstract : Amidst the crisis of instrumental reason, a number of contemporary political philosophers including Jürgen Habermas have sought to rescue the project of a reasonable humanism from the twin threats of religious fundamentalism and secular naturalism. In his recent work, Habermas defends a post-metaphysical politics that aims to protect rationality against encroachment while also accommodating religious faith within the public sphere. This paper contends that Habermas' post-metaphysical project fails to provide a robust alternative either to the double challenge of secular naturalism and religious fundamentalism or to the ruthless instrumentalism that underpins capitalism. By contrast with Habermas and also with the 'new realism' of contemporary political philosophers such as Raymond Geuss or Bernard Williams, realism in the tradition of Plato and Aristotle can defend reason against instrumental rationality and blind belief by integrating it with habit, feeling and even faith. Such metaphysical–political realism can help develop a politics of virtue that goes beyond communitarian thinking by emphasising plural modes of association (not merely 'community'), substantive ties of sympathy and the importance of pursuing goodness and mutual flourishing.